2003
DOI: 10.1152/jn.00467.2003
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization Block of Neurons During Maintenance of Electrographic Seizures

Abstract: Agopyan N and Avoli M. Synaptic and non-synaptic mechanisms underlying low calcium bursts in the in vitro hippocampal slice. Exp Brain Res 73: 533-540, 1988. Alarcon G, Binnie CD, Elwes RD, and Polkey CE. Power spectrum and intracranial EEG patterns at seizure onset in partial epilepsy. Electroencephalogr Clin Neurophysiol 94: 326 -337, 1995. Albrecht D, Rausche G, and Heinemann U. Reflections of low calcium epileptiform activity from area CA1 into dentate gyrus in the rat hippocampal slice. Brain Res 480: 393… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
83
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 50 publications
14
83
3
Order By: Relevance
“…The importance of PVBCs in seizure propagation has been recently demonstrated [65]. It was also reported that some neurons can enter into depolarization blocks during seizures [66,67]. We have to note however that the fate of dendritic inhibition is different.…”
Section: Generation Of Interictal Spikes: Changes In Cellular and Netmentioning
confidence: 76%
“…The importance of PVBCs in seizure propagation has been recently demonstrated [65]. It was also reported that some neurons can enter into depolarization blocks during seizures [66,67]. We have to note however that the fate of dendritic inhibition is different.…”
Section: Generation Of Interictal Spikes: Changes In Cellular and Netmentioning
confidence: 76%
“…In others, V m hyperpolarized to a pre-anoxic stage after hyperactivity and cells became quiescent. This does not necessarily imply that these neurons recovered from seizure as this can occur as a result of a depolarization block in which seizure can be maintained even in the absence of continuous neuronal firing (Bikson et al, 2003). While co-antagonism of GABA A and GABA B receptors induced paroxysmal depolarizing shift, blocking either GABA A or GABA B receptors alone did not cause catastrophic depolarization.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation the prolonged bursts are primarily synchronized on a slow time scale by transient increases in extracellular K + (Bikson et al, 2003b;Yaari et al, 1983) and on a faster time scale by ephaptic or field effect interactions (Frohlich and McCormick, 2010;Jefferys, 1995). The latter occur when the electrical currents generated by neuronal activity cause a transmembrane depolarization sufficient to nudge neighbouring neurons to threshold; this effect is relatively weak (Jefferys, 1981), but under conditions of heightened excitability, such as in low-Ca 2+ media or during epileptic discharges, neurons are close enough to threshold for this effect to impact on spike timing.…”
Section: Acute Models Of Epilepsy-convulsant Drugsand Changes In Extrmentioning
confidence: 99%